The effect of the reproductive health self-care educational booklet on the self-care ability of female university students - Mahshid AbdiShahshahani; Maryam Hashemi; Shahnaz Kohan (Iranian Journal of Nursing and Midwifery Research, 2023)
Background: Reproductive health during youth is considered one of the pivotal aspects of sustainable development. In this regard, students are more exposed to reproductive health problems and risks. Accordingly, the aim of this study was to determine the effect of the reproductive health self-care educational booklet on the self-care ability of female university students. Materials and Methods: This study was a quasiexperimental research in which a reproductive health self-care educational booklet designed based on needs assessment was provided to 75 newly admitted female university students at Isfahan University of Medical Sciences in 2018-2019 who were selected by quota sampling method from all faculties. Using a researcher-made questionnaire on reproductive health self-care ability (knowledge, attitude, practice), data were collected before, immediately after, and 6 weeks after the intervention. Data analysis was performed using descriptive and analytical statistics in SPSS version 20. Results: As the results showed, the mean score of self-care ability (F = 208.46, p < 0.001), knowledge (F = 130.88, p < 0.001), attitude (F = 76.09, p < 0.001), and practice (F = 89.76, p < 0.001) of the subjects immediately and 6 weeks after the intervention was significantly higher than before the intervention. However, no significant difference was observed in these scores, between immediately after and 6 weeks after the intervention. Conclusions: The results indicated that the designed self-care educational booklet led to a relatively constant promotion of the reproductive health self-care ability of female students. Thus, this booklet seems to be useful in meeting the educational needs of female students in various aspects of reproductive health.